2016
DOI: 10.1177/0363546516629418
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of the Mulligan Knee Taping Technique on Patellofemoral Pain and Lower Limb Biomechanics

Abstract: The Mulligan knee taping technique may benefit the clinical environment by providing an alternative evidence-based treatment plan for PFP.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
18
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 36 publications
2
18
0
2
Order By: Relevance
“…As the agreement between raters and binary outcomes was poor in light of good average measures inter-rater reliability further exploration was undertaken to try and explain this. The correlation found between hip internal rotation moment and SKB ratings may be representative of the valgus collapse type loading clinicians seek to modify [3,[38][39][40]. Negative correlation between extensor knee moment and SKB ratings likely represents a lack of ability to load normally through the patella tendon [41].…”
Section: Discussionmentioning
confidence: 91%
“…As the agreement between raters and binary outcomes was poor in light of good average measures inter-rater reliability further exploration was undertaken to try and explain this. The correlation found between hip internal rotation moment and SKB ratings may be representative of the valgus collapse type loading clinicians seek to modify [3,[38][39][40]. Negative correlation between extensor knee moment and SKB ratings likely represents a lack of ability to load normally through the patella tendon [41].…”
Section: Discussionmentioning
confidence: 91%
“…7 In a previous study, Mulligan taping applied from the neck of the fibula and passing anteriorly over the tibia to secure internal rotation of the tibia and ending on the anterolateral aspect of the femur decreased knee adduction and hip internal rotation during single-leg squats in young adults (aged 18-35 years) with patellofemoral pain. 19 As in the study by Hickey et al, 19 the taping procedure in the present study was designed to prevent or reduce tibiofemoral rotation at the knee joint. 13 Unlike the previous taping technique that optimizes the patellar tracking movement, NET does not entail contact with the patella.…”
Section: Discussionmentioning
confidence: 99%
“…14 Multiple anatomic, demographic, and physiologic factors have been associated with anterior knee pain. Rehabilitation programs, long considered the mainstay of treatment for anterior knee pain of insidious onset, have focused on abnormalities deemed modifiable or reversible with exercise-with foot orthoses, 2 knee orthoses, and tape application 11,13 sometimes playing a supporting role. A randomized trial from Denmark demonstrated the efficacy of a comprehensive exercise and education program for treating ''adolescent patellofemoral pain,'' compared with education alone.…”
Section: Editorialmentioning
confidence: 99%